LIFE OF MINE (LOM) SLOPE STABILITY ANALYSIS IN COAL MINING OPERATIONS OF PT ABC IN NORTH KALIMANTAN USING LIMIT EQUILIBRIUM METHOD - Agil Farhandi, Muhammad
The slope stability analysis aims to produce a Safety Factor value in accordance with KEPMEN No. 1827K/30/MEM/2018. This study analyzes the stability of operational slopes, such as high walls, low walls, side walls, and embankments at PT ABC using Rocscience Slide2 software under conditions of Hu at 0.8 and seismic loading of 0.025g. The analysis method uses the limit equilibrium method with the Janbu and Bishop sub-methods. The minimum criteria for the Safety Factor and Probability of Slope Failure are based on KEPMEN No. 1827K/30/MEM/2018. The results of the SF and PF calculations on the LOM operational slope design showed unsafe parameter values for all slopes, necessitating a redesign of the slope geometry. The soft clay material on the high wall and side wall was sloped to 35°, the soft clay material on the low wall was sloped to 20°, and the disposal material on the IPD was sloped to 25°. After the redesign, the slope stability parameters met the minimum values according to KEPMEN No. 1827K/30/MEM/2018.